2015
DOI: 10.1093/mnras/stv338
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear and extended infrared emission of the Seyfert galaxy NGC 2992 and the interacting system Arp 245

Abstract: We present subarcsecond resolution infrared (IR) imaging and mid-IR spectroscopic observations of the Seyfert 1.9 galaxy NGC 2992, obtained with the Gemini North Telescope and the Gran Telescopio CANARIAS (GTC). The N-band image reveals faint extended emission out to ∼3 kpc, and the PAH features detected in the GTC/CanariCam 7.5-13 µm spectrum indicate that the bulk of this extended emission is dust heated by star formation. We also report arcsecond resolution MIR and far-IR imaging of the interacting system A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 103 publications
(146 reference statements)
1
26
0
Order By: Relevance
“…Mrk 1066 was analyzed by Ramos and Alonso-Herrero et al (2014) to study the survival of the responsible molecules for the 11.3 µm PAH feature in the close vicinity of an AGN. García-Bernete et al (2015) studied the extended emission of NGC 2992 up to ∼3 kpc, finding that PAH features might indicate that the bulk of this extended emission is dust heated by SF. Esquej et al (2014) compared nuclear with larger apertures (using Spitzer spectra) in 12 of our sources to study the correlation between SFR through the 11.3 µm PAH feature and AGN accretion.…”
Section: Samplementioning
confidence: 99%
“…Mrk 1066 was analyzed by Ramos and Alonso-Herrero et al (2014) to study the survival of the responsible molecules for the 11.3 µm PAH feature in the close vicinity of an AGN. García-Bernete et al (2015) studied the extended emission of NGC 2992 up to ∼3 kpc, finding that PAH features might indicate that the bulk of this extended emission is dust heated by SF. Esquej et al (2014) compared nuclear with larger apertures (using Spitzer spectra) in 12 of our sources to study the correlation between SFR through the 11.3 µm PAH feature and AGN accretion.…”
Section: Samplementioning
confidence: 99%
“…This method has been widely tested in ground-based MIR images (e.g. Soifer et al 2000;Radomski et al 2002Radomski et al , 2003Levenson et al 2009;Ramos Almeida et al 2009, 2011aMason et al 2012;García-Bernete et al 2015;Martínez-Paredes et al 2015). The MIR nuclear fluxes calculated using this method are listed in Table 2.…”
Section: Subarcsecond Resolution Nuclear Fluxes: Subtraction Of Scalementioning
confidence: 99%
“…Considering the strong 6.2 and 11.3 µm PAH features seen in the Spitzer/IRS spectrum, the bulk of this extended emission is likely produced by dust heated by SF activity. See García-Bernete et al (2015) for a detailed study of this galaxy.…”
Section: Appendix C: Notes On Individual Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alonso-Herrero et al (2012) and García-Bernete et al (2015) found that the AGN emission does not dominate the 70 µm emission of NGC 1365 and NGC 2992, respectively. These two galaxies do not satisfy any of our selection criteria.…”
Section: Comparison With Other Workmentioning
confidence: 95%